Characterization of mycobacteria and mycobacteriophages isolated from compost at the São Paulo Zoo Park Foundation in Brazil and creation of the new mycobacteriophage Cluster U. Issue 1 (December 2016) - Lima-Junior, James; Viana-Niero, Cristina; Conde Oliveira, Daniel; Machado, Gabriel; Rabello, Michelle; Martins-Junior, Joaquim; Martins, Layla; Digiampietri, Luciano; da Silva, Aline; Setubal, João; Russell, Daniel; Jacobs-Sera, Deborah; et al.
Abstract Background A large collection of sequenced mycobacteriophages capable of infecting a single host strain ofMycobacterium smegmatis shows considerable genomic diversity with dozens of distinctive types (clusters) and extensive variation within those sharing evident nucleotide sequence similarity. Here we profiled the mycobacterial components of a large composting system at the São Paulo zoo. Results We isolated and sequenced eight mycobacteriophages usingMycobacterium smegmatis mc2 155 as a host. None of these eight phages infected any of mycobacterial strains isolated from the same materials. The phage isolates span considerable genomic diversity, including two phages (Barriga, Nhonho) related to Subcluster A1 phages, two Cluster B phages (Pops, Subcluster B1; Godines, Subcluster B2), three Subcluster F1 phages (Florinda, Girafales, and Quico), and Madruga, a relative of phage Patience with which it constitutes the new Cluster U. Interestingly, the two Subcluster A1 phages and the three Subcluster F1 phages have genomic relationships indicating relatively recent evolution within a geographically isolated niche in the composting system. Conclusions We predict that composting systems such as those used to obtain these mycobacteriophages will be a rich source for the isolation of additional phages that will expand our view of bacteriophage diversity and evolution.